Ultra-High Field 7-Tesla Magnetic Resonance Imaging and Electroencephalography Findings in Epilepsy. Issue 2 (May 2022) - Salehi, Fateme; Nadeem, Ibrahim M.; Kwan, Benjamin Y. M.; Mirsattari, Seyed M.; Lee, Donald H.; Burneo, Jorge G.; Steven, David; Hammond, Robert; Peters, Terry M.; Khan, Ali R.
Purpose: Assessment of patients for temporal lobe epilepsy (TLE) surgery requires multimodality input, including EEG recordings to ensure optimal surgical planning. Often EEG demonstrates abnormal foci not detected on 1.5T MRI. Ultra-high field MRI at 7T provides improved resolution of the brain. We investigated the utility of 7T MRI to detect potential anatomical abnormalities associated with EEG changes. Methods: Ultra-high field data were acquired on a 7T MRI scanner for 13 patients with history of drug resistant TLE who had had EEG telemetry recordings. Qualitative evaluation of 7T imaging for presence of focal abnormalities detected on EEG was performed. Correlation of 7T MRI findings with EEG recordings of focal slowing or interictal epileptic spikes (IEDs), and seizures was performed. Results: Assessment of 7T MRI demonstrated concordance with TLE as determined by the multidisciplinary team in 61.5% of cases (n = 8). Among these, 3 patients exhibited supportive abnormal 7T MRI abnormalities not detected by 1.5T MRI. In patients who underwent surgery, 72.7% had concordant histopathology findings with 7T MRI findings (n = 8). However, qualitative assessment of 7T images revealed focal anatomical abnormalities to account for EEG findings in only 15.4% of patients (n = 2). Other regions that were found to have localized IEDs in addition to the lesional temporal lobe, included the contralateral temporal lobe (n = 5), frontal lobe (n = 3), and parieto-occipital lobe (n = 2). Conclusion: Ultra-high field 7T MRI findings show concordance with clinical data. However, 7T MRI did not reveal anatomical findings to account for abnormalities detected by EEG.